The Significance of Holistic Spirituality in Sunan Kalijaga’s Kidung Rumekso Ing Wengi - Lestari, Sri (Jurnal Lingua Idea, 2024)
This research aims to explain the holistic spirituality of Kidung Rumekso ing Wengi by Sunan Kalijaga. In addition to being used in various situations to pray, the song needs to be studied for the sake of cultural preservation, historical understanding, literary wealth, identity, and local pride. This study is qualitative. The data used in this study consisted of documents and interviews. Data was collected through interviews and document analysis. The data validation technique uses triangulation of theory and method, while the data analysis technique uses Miles and Hubermann's interactive model and Roland Barthes' markers. Based on interviews with sources and literature studies, Kidung Rumekso ing Wengi is a counter-acceptance mantra taught by Sunan Kalijaga to his followers. Until now, there are still people who have developed hymns and the practice of hymns as a medium of prayer by paying attention to aspects of tolerance. There are various values, such as the ethics of vigilance, returning to Allah, the ethics of prayer, and self-control.